Avaliaç\~ao de efeitos do Programa Profrota Pesqueira sobre indicadores do mercado de trabalho - Felipe Garcia Ribeiro; Patrízia Raggi Abdallah; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– We investigate the effects of the Profrota Pesqueira Program, created in 2004, on the performance of labor market indicators of municipalities with port fishing terminals. Specifically, we measure the effects on the formal employment and earnings. To do so, we combine employment information from Rais between 2000 and 2015, with data from other sources for obtaining a panel of municipalities. We used Difference in Differences Estimator. The results show that the program did not have positive effects on the indicators evaluated in the fisheries sector. Some of the estimates are robust to analyzes of falsification. Econometric analysis of the effects of the program on the labor market as a whole, with data from the population census, editions 2000 and 2010, reveals that the program seems to have influenced the engagement of workers in paid labor market activities and to reduce labor in own consumption or in the non paid labor market activities.
Keywords: C21; J21; J31; 330; Profrota Pesqueira; impact evaluation; diference in differences; labor market